The Relationship of Keygel Exercises With the Healing of Perineal Wounds in Partworse Mothers With Normal Delivery - Rismeni Saragih (International Journal of Health and Social Behavior, 2024)
This study examines the relationship between Kegel exercises and the healing of perineal wounds in postpartum mothers who underwent normal delivery. Perineal wounds, a common outcome of vaginal childbirth, can lead to discomfort and complications if not properly managed. Kegel exercises, known for strengthening the pelvic floor muscles, may also play a crucial role in accelerating the healing process of perineal wounds. This research involved a sample of postpartum mothers who were instructed to perform Kegel exercises regularly. Data were collected through clinical observations and self-reported healing experiences over a specified period. The findings indicate a significant positive correlation between the regular practice of Kegel exercises and the expedited healing of perineal wounds. Mothers who adhered to the exercise regimen reported reduced pain, faster wound closure, and improved overall postpartum recovery. These results suggest that Kegel exercises should be recommended as a routine postpartum practice to promote faster healing and enhance the well-being of new mothers. Further research is recommended to explore the underlying mechanisms and to establish standardized guidelines for the implementation of Kegel exercises in postpartum care.